Application of derm dotting in oral and maxillofacial surgery. Issue 1 (29th June 2015) - Van Hevele, J.; Hauben, E.; Haspeslagh, M.; Agbaje, O.; Salem, A.; Schoenaers, J.; Politis, C.
Abstract: Purpose : Derm dotting is a new method of marking skin biopsies, and it is used by dermatopathologists to identify most diagnostic tissues on a microscopic slide. This method uses nail varnish to mark specific lesions and suspected section planes, or to orient skin resections. The nail varnish is resistant to different tissue processes, discernible while cutting the tissue block, and easily recognizable under the microscope. We examined the effectiveness of derm dotting on intraoral tissues. Methods : We used the derm‐dotting technique on the intraoral tissues of nine patients who underwent resection of a squamous carcinoma. We also tested this method on frozen sections. Results : In all cases of resected tissue, the nail varnish was visible under gross examination, traceable while cutting the tissue block, and clearly visible in the definitive sections. The dots were preserved in the frozen sections, but they were lost in half of the decalcified tissues. Conclusions : Derm dotting is an inexpensive, simple method that can replace the stitching technique used by surgeons to orient specimens. The stitches have to be removed by the pathologist, therefore possibly creating an artifact in the biopsy. The varnish dots or lines can be used to orient the specimen. In addition, the dots can easily mark suspect borders or areas of interest to be examined by the pathologist, using different colors, if desired. With derm dotting, the pathologist receives a more representative slide enabling a more accurate clinicopathological correlation.